2011
DOI: 10.1186/1479-5876-9-208
|View full text |Cite
|
Sign up to set email alerts
|

Definition of the viral targets of protective HIV-1-specific T cell responses

Abstract: BackgroundThe efficacy of the CTL component of a future HIV-1 vaccine will depend on the induction of responses with the most potent antiviral activity and broad HLA class I restriction. However, current HIV vaccine designs are largely based on viral sequence alignments only, not incorporating experimental data on T cell function and specificity.MethodsHere, 950 untreated HIV-1 clade B or -C infected individuals were tested for responses to sets of 410 overlapping peptides (OLP) spanning the entire HIV-1 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
201
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(214 citation statements)
references
References 56 publications
11
201
2
Order By: Relevance
“…We focused on mutations at 23 residues in Gag-p24 to evaluate aspects of our initial design of a Gag-p24 "conserved-element" (CE) vaccine (3,32,33). This immunogen includes 7 segments that are composed of sites conserved in ϳ98% of circulating sequences, allowing one site per element to be more variable ("toggle" site) if the two residues together represent Ͼ99% of the known viral genetic variation.…”
mentioning
confidence: 99%
“…We focused on mutations at 23 residues in Gag-p24 to evaluate aspects of our initial design of a Gag-p24 "conserved-element" (CE) vaccine (3,32,33). This immunogen includes 7 segments that are composed of sites conserved in ϳ98% of circulating sequences, allowing one site per element to be more variable ("toggle" site) if the two residues together represent Ͼ99% of the known viral genetic variation.…”
mentioning
confidence: 99%
“…The most successful expression of full-length Pr 55 Gag precursor polyprotein to date was done with subtype B HIV-1 Gag in transplastomic tobacco, with yields of enveloped~100 nm diameter VLPs of up to 400 mg/kg biomass [117]. This was close to 10 000-fold more than a previous best by our group, with VLPs produced in transgenic tobacco [81], and represents a viable yield for a product with serious vaccine potential: recent evidence that lack of progression to AIDS is linked to strong CTL responses to Gag [118][119][120] reinforces the need for vaccines that can target such responses, and Pr 55 Gag VLPs are potent elicitors of CTL, especially when used as a protein boost to a heterologous prime in primate models [121,122]. A recent paper details how HIV-1 p24 antigen expressed transgenically in either Arabidopsis thaliana or Daucus carota showed a priming effect in mice fed whole plant material, eliciting humoral immune responses detected as serum anti-p24-specific IgG after an intramuscular purified p24 protein boost [123].…”
Section: Hiv Vaccinesmentioning
confidence: 89%
“…The other chimaeric L1s did not form distinct particles, and elicited significantly weaker humoral immune responses for the same dose of protein. The L1:L2 [108][109][110][111][112][113][114][115][116][117][118][119][120] particle formation was in contrast to repeated previous expression of this and the other chimaeras in insect cells, where only loose aggregates of capsomers were formed for L1:L2 [108][109][110][111][112][113][114][115][116][117][118][119][120] [95,96].…”
Section: Papillomavirus Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent mosaic vaccine described by Ondondo et al 51,. included regions were restricted not only by being the most conserved regions, but were further limited to include only regions that spanned epitopes that were deemed protective, in that responses to these epitopes were associated with low viral loads in natural infections 54. Indeed, it was found that infected people with enriched responses to epitopes embedded in the second‐generation conserved region vaccine had lower viral loads, supporting the utility of the strategy of immune response focusing 51…”
Section: T‐cell Vaccine Design Strategiesmentioning
confidence: 97%